1997
DOI: 10.1143/jjap.36.991
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Annealing of Dangling Bonds in a-Si:H

Abstract: We have investigated the kinetics of light-induced defect (dangling bond) creation and annealing processes in a-Si:H containing a large amount of hydrogen at 300 K and 77 K using the ESR technique. We have obtained direct evidence for the light-induced annealing of dangling bonds at 300 K. A model, in which nonradiative recombination of electrons and holes at hydrogen-related dangling bonds is taken into account, is presented to interpret the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…They suggested a model based on the stretched exponential degradation that consists of two different stretched exponential components with a different τ. Takeda et al suggested a model with a more practical view. 23) They fabricated a-Si:H samples having unusually high hydrogen content between 22-36 at. %, and light-soaked at various intensities.…”
Section: Self-healing and Effect Of Initial Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested a model based on the stretched exponential degradation that consists of two different stretched exponential components with a different τ. Takeda et al suggested a model with a more practical view. 23) They fabricated a-Si:H samples having unusually high hydrogen content between 22-36 at. %, and light-soaked at various intensities.…”
Section: Self-healing and Effect Of Initial Degradationmentioning
confidence: 99%
“…An interesting aspect is that the irreversible changes in the light-induced degradation kinetics of pm-Si:H PIN solar cells can be explained by recalling the hydrogen evolution from internal surfaces. 23) Figure 4 shows the H 2 partial pressure detected during hydrogen effusion, normalized to the volume of the sample, as a function of temperature for a-Si:H and pm-Si:H PIN layer stacks on Corning glass. The hydrogen effusion spectrum of the as-deposited pm-Si:H PIN layer stack [Fig.…”
Section: Hydrogen Effusion: Modification Of Hydrogen Bonding On Silic...mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be supported by a moleculardynamics simulation which suggests that a light-induced defect is nucleated by a localized defect state (Fedders et al 1992). Note that the photoinduced annealing of defects, as shown by curve (b) in ® gure 1, has been observed for a-Si : H with a very high density of defects (Takeda et al 1997), which may occur for the condition k ¸N < 0.…”
mentioning
confidence: 91%
“…ESR measurements of the virtually identical hydrogenated/deuterated a-Si:H/D and µc-Si:H/D indicate that the features in the spectra of the irradiated material belong to a hydrogen-related hyperfine pattern. The nature of this center is discussed in the light of known H-related complexes found in c-Si [14][15][16][17] and suggested H-related db states in a-Si:H [32,33].…”
Section: Introductionmentioning
confidence: 99%